The judicial power of the purse how courts fund national defense in times of crisis - Staudt, Nancy (Chicago, Ill. : University of Chicago Press, 2011)
Congress and the president are not the only branches that deal with fiscal issues in times of war. In this innovative book Nancy Staudt focuses on the role of federal courts in fiscal matters during warfare and high-cost national defense emergencies.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: United States. -- Supreme Court -- Powers and duties -- Economic aspects; War and emergency legislation -- Economic aspects -- United States; Judicial power -- Economic aspects -- United States; Judge-made law -- Economic aspects -- United States; Fiscal policy -- United States; Law; United States of America, USA; Constitution: government & the state; Warfare & defence; Jurisprudence & general issues; Legal systems: judicial powers